Implementación de incentivos no económicos para la mejora del desempeño laboral en el área de prevención de Saga Falabella 2016 - Díaz Linares, Hedder Joao (2017)
The purpose of this study was to determine the influence of an implementation of noneconomic incentives to improve work performance in the area of prevention of Falabella Saga 2016. The problem was related to the following question: How the implementation of incentives will improve the work performance of the Falabella Trujillo 2016 Saga prevention area, whose hypothesis was: The implementation of non-economic incentives will progressively improve the work performance of the Falabella Trujillo 2016 Saga prevention area; highlighting as an independent variable, non-economic incentives and as a dependent variable the labor performance. Likewise, the general objective was to propose the implementation of non-economic incentives to improve the performance of personnel in the loss prevention area of Falabella Trujillo Saga. It had a total population of 38 employees so the sample is non-probabilistic. The research design used was nonexperimental. As a data collection research technique, I applied the questionnaire to the personnel of the loss prevention area, where they answered that they would like to receive some kind of non-economic incentive as a result of good job performance and also direct observation. And finally, the conclusion reached was that incentives for training and recreational activities are the least preferred by staff, so that the staff has a commitment to the company, feel identified and provide the best of yes, it is recommended to evaluate them with the non-economic incentives they would prefer.